2010
DOI: 10.5251/abjna.2010.1.5.1057.1060
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding Gliricidia Leaf Meal (GLM) on the haematological, serological and carcass characteristics of weaned rabbits in the tropics

Abstract: In an experiment to determine the effect of feeding graded levels of Gliricidia sepium Leaf Meal (GLM) on the heamatology, serum chemistry and carcass characteristics of rabbits in the tropics, twenty-five (25) weaned rabbits of mixed sexes, 5-6 weeks old, were randomly allotted to five (5) dietary treatments in which GLM replaced soybean meal (SBM) at 0% (control), 5%, 10%, 15% and 20% with five (5) rabbits per treatment in a completely randomised design. Each rabbit constituted a replicate. Haematological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
5
4
0
1
Order By: Relevance
“…The lower relative weight of the shoulder compared to the thigh might be attributed to the late maturing characteristics of the shoulder, especially the scapular region (Ijaiya and Fasanya, 2004). The findings from this study agree with the works of previous researchers on the use of various agro-industrial byproducts and wastes in place of maize grain in rabbit's diets (Odeyinka et al, 2007;Adeyemi et al, 2010;Olorunsanya et al, 2007;Njidda and Isidahomen, 2011;Amata, 2010). The non-significant difference (P > 0.05) obtained in these parameters suggest that millet offal had no dire consequence on the rabbit's carcass cuts.…”
Section: Carcass Evaluationsupporting
confidence: 93%
See 2 more Smart Citations
“…The lower relative weight of the shoulder compared to the thigh might be attributed to the late maturing characteristics of the shoulder, especially the scapular region (Ijaiya and Fasanya, 2004). The findings from this study agree with the works of previous researchers on the use of various agro-industrial byproducts and wastes in place of maize grain in rabbit's diets (Odeyinka et al, 2007;Adeyemi et al, 2010;Olorunsanya et al, 2007;Njidda and Isidahomen, 2011;Amata, 2010). The non-significant difference (P > 0.05) obtained in these parameters suggest that millet offal had no dire consequence on the rabbit's carcass cuts.…”
Section: Carcass Evaluationsupporting
confidence: 93%
“…The values for albumin and globulin ranged from 2.85 to 3.10 and 1.83 to 2.02 g/dl, respectively. These values were close to the values of 2.5 to 4.0 g/dl for albumin obtained by Anon (1980), 2.75 to 2.84 g/dl by Amata (2010), 2.2 to 4.2 g/dl by Njidda and Isidahomen (2011); and 1.57 to 2.15 g/dl for globulin (Amata, 2010) and 1.3 to 2.0 g/dl (Njidda and Isidahomen, 2011) for rabbits of similar weight. The values obtained for the albumin and serum globulin, were within the ideal range for rabbit healthy development (Anon, 2004;RAR, 2007).…”
Section: Serum Metabolitessupporting
confidence: 90%
See 1 more Smart Citation
“…These values, except the protein content fell within the range of nutrients early reported for G. sepium by [20]. Actually, its protein content is lower than values observed by [20], [21], [22], [23], [24]; meanwhile it is higher than that obtains by [25] in Nigeria. So, if the constraints militating against the enhanced utilisation of the leaf of G. sepium are handled, that is its content of anti-nutritional factors, it may provide valuable unconventional alternative feedstuff for domestic animals especially monogastrics that exert high demand on nutrients particularly energy, protein and micronutrients.…”
Section: A Chemical Composition Of Gliricidia Leaf Meal (Glm)supporting
confidence: 73%
“…This is in agreement with what Etim and Oguike () and Mandour, Al‐Shami, and Hussein () reported in trials with rabbits fed different unconventional diets. On the contrary, Igwebuike, Anugwa, Raji, Ehiobu, and Ikurior () and Amata () reported that most haematological parameters were affected by feed with unconventional diets and related this change in parameters to the presence of toxic substances in the ingredients tested. The differences in FBN values between A160 and A320 diets were not related to the proportion of A. dubius , because in both diets, FBN levels were similar to the A0 diet.…”
Section: Discussionmentioning
confidence: 99%